Decreased handgrip strength in patients with type 2 diabetes: A cross-sectional study in a tertiary care hospital in north India. Issue 1 (January 2021) - Kaur, Parjeet; Bansal, Ritesh; Bhargava, Bharti; Mishra, Sunil; Gill, Harmandeep; Mithal, Ambrish
Abstract: Background and aims: Type 2 diabetes mellitus (T2DM) has been associated with low muscle mass and strength. India has second highest number of diabetes cases worldwide. Till date, muscle mass and strength of Asian Indians with T2DM are not well studied. Aim of the study was to compare the skeletal muscle mass and muscle strength between individuals with and without T2DM. Methods: This cross-sectional study, included subjects with T2DM, age 18–70 years and age and sex-matched individuals without diabetes (controls). Body composition was assessed using Inbody 570 body composition analyser. Hand grip strength (HGS) was measured using JAMAR's Hydraulic Hand Dynamometer. Results: Total of 194 subjects (95 T2DM and 99 controls) were studied. Mean HGS (kg) was significantly lower both in men and women with diabetes compared with controls (32.4 ± 7.9 vs 37.9 ± 8.1, p = 0.001 in men and 20.6 ± 6.4 vs 23.1 ± 4.06, p = 0.02 in women). Significantly higher percentage of men and women with diabetes had sarcopenia compared with controls (44.4% vs 15.1% in men and 51% vs 20% in women). In multivariate logistic regression analysis, diabetes was an independent risk factor for low HGS in both men (OR = 6.6) and women (OR = 3.4) after adjusting for age, smoking, alcohol consumption, obesity, physical activity and dietary protein intake. Conclusion: HGS was significantly lower in subjects with T2DM compared with subjects without diabetes. Diabetes was an independent risk factor for low HGS. Highlights: Hand grip strength was significantly lower in subjects with T2DM compared with age and sex matched subjects without diabetes. Significantly higher percentage of men and women with diabetes had sarcopenia (using HGS criteria) compared with controls. Diabetes was an independent risk factor for low HGS in both men and women.